Patterns of complexity of urinary stone disease based on anatomical sites and stone number: A study conducted among the patients who underwent surgical intervention at Genitourinary Surgical unit, Teaching Hospital, Jaffna - Sivarangini, S.; Arasaratnam, V.; Sathesan, B.; Gunatilake, M.; Kandeepan, K. (University of Jeyewardenepura, 2018)
Urinary stones are commonly formed in the kidney and urinary bladder. Rarely stones can form in the ureter and urethra when functional or anatomical defects are present in the urinary tract. Mode of presentation of disease, morbidity and mortality, type of intervention required, rate of stone clearance after intervention, urgency of intervention and selection of anatomical site for intervention depends on anatomical site and stone burden.